Attack‐parameter‐dependent state feedback controller design for stochastic systems with denial‐of‐service attacks. (9th November 2022) - Chen, Xiaoli; Hu, Songlin; Li, Jianrui; Hu, Chunyang; Xie, Xiangpeng; Zhang, Jing
Abstract: In this article, we investigate the attack‐parameter‐dependent controller synthesis problem for a class of stochastic control system under aperiodic denial‐of‐service (DoS) attacks. Different from the classic DoS attack models, which are characterized by DoS frequency and DoS duration, a new type of time‐constrained DoS attack model that only restricts the upper and lower bounds of the sleeping and active periods of the DoS attacker is introduced. Considering the effect of such DoS attacks, a switching‐like stochastic system model is built. Then based on the attack‐parameter‐dependent time‐varying stochastic Lyapunov function method, a new mean square exponential stability criterion of the resulting stochastic system under the DoS attacks is formulated in the form of linear matrix inequalities. Also, the attack‐resilient H ∞ $$ H_{∞ } $$ controller is designed. Finally, taking an aircraft system as an example, the validity of the obtained theoretical results is verified.